2019
DOI: 10.1097/jhq.0000000000000160
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perspectives on Reasons for Unplanned Readmissions

Abstract: Massachusetts has one of the highest rates of 30-day readmissions in the country. To identify patient-reported factors that may contribute to readmissions, we conducted semi-structured interviews with patients with unplanned readmissions within 30 days of inpatient discharge from the medicine services at an urban medical center between June and August 2016. Interviews with patients and/or proxies were conducted in English, Spanish, Mandarin, or Cantonese, then translated to English if necessary, transcribed ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…20 A recent study where 36 medical patients who experienced unplanned hospital readmission within 30 days were interviewed showed that many patients attributed their readmission to underlying illness. 21 Although 63% did not identify factors they thought could have prevented hospital readmission, communication deficits between health professionals, and between health professionals and patients, was a dominant theme. 21 Despite having important perspectives to offer, the patient and carer view of early unplanned hospital readmissions is underreported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 A recent study where 36 medical patients who experienced unplanned hospital readmission within 30 days were interviewed showed that many patients attributed their readmission to underlying illness. 21 Although 63% did not identify factors they thought could have prevented hospital readmission, communication deficits between health professionals, and between health professionals and patients, was a dominant theme. 21 Despite having important perspectives to offer, the patient and carer view of early unplanned hospital readmissions is underreported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…21 Although 63% did not identify factors they thought could have prevented hospital readmission, communication deficits between health professionals, and between health professionals and patients, was a dominant theme. 21 Despite having important perspectives to offer, the patient and carer view of early unplanned hospital readmissions is underreported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The study team developed and adapted the interview guide (Supplemental Fig 2) on the basis of the analysis from the team' s previous study of adult readmissions. 22 The adult interview guide had been developed with input from multiple stakeholders, including the hospital' s Patient and Family Advisory Council and Readmissions Task Force, which consisted of physicians, nurses, pharmacists, case managers, social workers, quality-improvement experts, and patient relations representatives. Questions probed patient and/or family experiences with original discharge, reasons for return to the hospital, adequacy of home care, and socioeconomic resources.…”
Section: Data Collectionmentioning
confidence: 99%
“…Despite a universal health insurance system that is compulsory and that covers ambulatory and hospital care, some services, such as home care services after hospital discharge, are not covered in Switzerland, which makes financial resources a precondition for access to professional home care. Poor communication between different health care providers and patients/proxies (25) or the lower likelihood of seeing a primary care provider or the appropri-ate specialist after discharge from hospital (26) have also been observed, especially for patients from ethnic minorities or/and with limited language skills. (13,20,based on 27) Despite this knowledge, the effects of social factors on unplanned readmission rates of the chronically ill have been studied insufficiently and study results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%